The Effect of Financial Performance on Sustainable Growth Rate - Pandiangan, Tumpal; Nurmayanti, Poppy; Savitri, Enni (Indonesian Journal of Economics, Social, and Humanities, 2025)
The effect of financial performance on the sustainable growth rate (SGR) is generally positive and significant. Financial performance, which reflects a company's profitability and efficiency, plays a crucial role in enabling a company to grow sustainably without relying excessively on external capital. Companies with better financial performance tend to have higher sustainable growth rates, indicating they can fund growth internally through retained earnings and efficient financial management. This study aims to analyze the effect of financial performance (liquidity ratio, solvency ratio, activity ratio, and Market Prospect Ratio) on sustainable growth rates. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2021, namely 269 companies. Sampling in this study used the purposive sampling method, so that of the 269 population only 47 companies fulfilled the sampling criteria. This study used multiple linear regression as a research data analysis tool. The results showed that the liquidity ratio, solvency ratio, and Market Prospect Ratio have a negative effect on the sustainable growth rate (SGR). While the activity ratio has a positive effect on the sustainable growth rate (SGR).